Walk softly on this heart of mine : a novel - Collins, Callie (Doubleday, 2025)
"Against the vibrant, bluesy backdrop of 1970s Austin, Texas, this shimmering debut follows the collision between hicks and hipsters that ultimately results in tragedy"--